2013
DOI: 10.1614/wt-d-12-00113.1
|View full text |Cite
|
Sign up to set email alerts
|

Palmer Amaranth (Amaranthus palmeri): A Review

Abstract: In little over 20 yr, Palmer amaranth has risen from relative obscurity to its current status as one of the most widespread, troublesome, and economically damaging agronomic weeds in the southeastern U.S. Numerous factors have enabled Palmer amaranth to become such a dominant and difficult-to-control weed, including its rapid growth rate, high fecundity, genetic diversity, ability to tolerate adverse conditions, and its facility for evolving herbicide resistance. It is both a serious threat to several U.S. cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
349
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(379 citation statements)
references
References 109 publications
4
349
0
8
Order By: Relevance
“…However, apparently this is not the case for glyphosate-resistant Palmer amaranth. A previously published work suggests the existence of different resistance mechanisms among A. palmeri biotypes (Ward et al, 2013). In laboratory experiments, Culpepper et al (2006) found no differences in glyphosate absorption and translocation between resistant and susceptible biotypes, but shikimate accumulation was not detected in tissues of y = a/(1+(x/b) c ) ou y = P mín + a/(1+(x/b) c ); DAA -days after application; * significant at 1% probability level.…”
Section: Results E Discussionmentioning
confidence: 94%
“…However, apparently this is not the case for glyphosate-resistant Palmer amaranth. A previously published work suggests the existence of different resistance mechanisms among A. palmeri biotypes (Ward et al, 2013). In laboratory experiments, Culpepper et al (2006) found no differences in glyphosate absorption and translocation between resistant and susceptible biotypes, but shikimate accumulation was not detected in tissues of y = a/(1+(x/b) c ) ou y = P mín + a/(1+(x/b) c ); DAA -days after application; * significant at 1% probability level.…”
Section: Results E Discussionmentioning
confidence: 94%
“…Palmer amaranth, redroot pigweed, and velvetleaf infestations occur in soybean fields throughout the eastern U.S. [2] [3] [4]. The weeds produce numerous seeds and establish large populations in soybean fields, thus reducing yields.…”
Section: Introductionmentioning
confidence: 99%
“…is highly competitive at the beginning of the cropping season, and a critical weed-free period of 9 weeks after planting is required to avoid yield loss (Keeley and Thullen, 1991). However, weeds like A. palmeri can be detrimental even at later stages of crop growth, as substantial seed production is possible even under competitive environments (Ward et al, 2013). A. palmeri can significantly shade cotton and prevent it from reaching its full yield potential (Morgan et al, 2001).…”
Section: Weed Flora and Their Competitiveness In Cottonmentioning
confidence: 99%